HUKUM ISLAM TERHADAP PREDATORY PRICING PADA PERSAINGAN USAHA JUAL BELI BUKU SECARA ONLINE: (Studi Kasus di Toko Buku Online SBG Book Store dan Toko Buku Online Wasilah) - Kasrokhim, Juni M. Thoha Ash Shofari; M. Chamim; Afif, Abdullah (Irtifaq, 2022)
This article discusses Predatory pricing that is carried out by business actors in selling products at prices below production costs at the SBG Book Store online store and Wasilah Online Bookstore. This study uses a qualitative approach, the data sources used are primary data and secondary data, data collection methods are interviews, observations and then analyzed by descriptive methods. The result of this research is that the practice of predatory pricing or selling at a loss carried out by new competitors in the buying and selling business will lead to injustice felt by other entrepreneurs, especially entrepreneurs who have been playing in the market for a long time. The similarities between the two stores are Knowing predatory pricing, Knowing that predatory pricing is a prohibited agreement, Knowing that sales and loss agreements in Islam are not allowed Using an online practice system. The difference between the two stores is in their sales system, customers, and marketing strategy. Keywords: Islamic Law, Predatory pricing, Selling and Loss